If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + (-1b + -1c) = 0 Remove parenthesis around (-1b + -1c) a + -1b + -1c = 0 Solving a + -1b + -1c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. a + -1b + b + -1c = 0 + b Combine like terms: -1b + b = 0 a + 0 + -1c = 0 + b a + -1c = 0 + b Remove the zero: a + -1c = b Add 'c' to each side of the equation. a + -1c + c = b + c Combine like terms: -1c + c = 0 a + 0 = b + c a = b + c Simplifying a = b + c
| 450-2X+X^2=0 | | 2(x+4)(3x+1)=0 | | 2x^2-8x-120= | | 108x+4=59x-2 | | (2t-4)/(t^2-4) | | 4x-5(4)=20 | | 6x+2=122 | | X^2-30x+207=0 | | (11z-2)(10z+9)=0 | | 24x^2-4x^3=0 | | (X^2+3x)-(x+4)(3x+8)=(3x+8)(x+3) | | (3b-4)-(-5b+3)= | | 2.4/3 | | 5x^2-8x+4=628 | | ln*4+ln*x=ln*7+ln(2x-2) | | 19=17-2x+5x | | 5-2x=3+2x+2 | | 8B+7X=5A | | 7X+8B=5A | | 4x=20+5x | | -1/3m-7=4 | | 0.7+0.05y=0.715 | | x^4-x^3-2x^2= | | 4a+8=11 | | 18(4c-1)-16=70c+18 | | 2x^2-4x+4=628 | | -3-4x=8x-39 | | 5/9(x-32)=25 | | 8x+13=6x-11 | | x+x-2=628 | | 4+x=180-3x | | Xsquared+5x+10=4 |